2002
DOI: 10.1017/s1481803500006345
|View full text |Cite
|
Sign up to set email alerts
|

Can body temperature be maintained during aeromedical transport?

Abstract: Background: Aeromedical transport in northern areas may be associated with hypothermia. The objective of this study was to determine whether significant hypothermia (core temperature <35ºC) occurs in severely injured or ill intubated patients during transport by rotary wing aircraft. Methods: In this prospective cohort study, all intubated patients over 16 years of age who were transported by rotary wing aircraft from rural hospitals or trauma scenes in northern Alberta to regional hospitals in Edmonton were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
5
8
1
Order By: Relevance
“…Watts et al found a reduction in temperature, 9 while Hatfield and Sookram reported no significant relationship between air transportation and temperature change. 10 Our subgroup of patients that did undergo heat loss are a cause for concern, mirroring the findings of Watts et al 9 The known benefits of centralized trauma care will continue to increase the demand for helicopter retrieval. Our results highlight the need to assess each patient's likelihood of hypothermia and use this as a prompt to optimize the patients' resuscitation before and during their transfer to definitive care.…”
supporting
confidence: 69%
“…Watts et al found a reduction in temperature, 9 while Hatfield and Sookram reported no significant relationship between air transportation and temperature change. 10 Our subgroup of patients that did undergo heat loss are a cause for concern, mirroring the findings of Watts et al 9 The known benefits of centralized trauma care will continue to increase the demand for helicopter retrieval. Our results highlight the need to assess each patient's likelihood of hypothermia and use this as a prompt to optimize the patients' resuscitation before and during their transfer to definitive care.…”
supporting
confidence: 69%
“…Studies to date have reported adverse temperature changes in trauma patients during helicopter transfer. 27,28 If hypothermia is confirmed by the EMS, this should ideally trigger active rewarming already in the pre-hospital environment. This is an attractive option, as a transportation time of around 30 min can hardly be expected to be much shortened in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another six patients with ISS < 9 were subsequently excluded, leaving 22 patients (14 males and eight females) for the final analysis. Median age was 27 years (IQR 19-55), median ISS was 21 (IQR [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and the median NISS was 25.5 (IQR 17-36). Three patients died prior to hospital discharge.…”
Section: Participantsmentioning
confidence: 99%
“…However, the flight duration in previous studies was relatively short (range, 18-35 min) [1][2][3][4]6]. Also, the evaluated outcome in previous studies was body temperature change between before and after air transport.…”
Section: Introductionmentioning
confidence: 99%
“…Air medical transport is common in emergency settings and is now the global standard. Although ambient air temperature decreases with altitude, several studies showed that the body temperature of most adult patients did not decline significantly during air medical transport [1][2][3][4][5][6]. Studies also show that body temperature change is not associated with flight duration [1,2,5,6] and outside air temperature [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%